APPROACHES TO THE STANDARDIZATION OF THE CHAMOMILE FLOWERS (CHAMOMILLAE RECUTITA FLORES) IN THE RUSSIAN AND FOREIGN PHARMACOPOEIAS - E. Y. Zagorulko; M. G. Ozhigova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
The article describes approaches to standardization of chamomile flowers in European Pharmacopoeia, British Pharmacopoeia, United States Pharmacopoeia, and State Pharmacopoeia thirteenth edition (SP XIII).The aim of this work is to analyze the quality requirements among Russian pharmacopoeia and foreign pharmacopoeias for medicinal plant raw material (MPRM) - chamomile flowers.Materials and methods. Monographs about chamomile flowers, which are found in the current editions of the Russian pharmacopoeia and the world's major pharmacopoeias were the objects of the study. A comparative analysis of the quality parameters specified in the monographs was carried out. Quality requirements for the essential oil and fluid extract of chamomile given in the European and British pharmacopoeias were also analyzed.Results and discussion. Some differences in the approaches to the standardization of chamomile flowers in the pharmacopoeias of different countries were revealed. SP XIII contains a more detailed description of the diagnostic signs of this MPRM and its impurities. According to the SP XIII, flavonoids are the main groups of biologically active substances (BAS) for MPRM identification, while other pharmacopoeias declare essential oil as a main BAS of chamomile flowers. Meanwhile, the composition of the essential oil components is different in European, British, and the United States Pharmacopeias. There is a tendency for the foreign pharmacopoeias to quantify the individual compounds, whereas in SP XIII chamomile flowers are standardized by the amount of BAS of different groups. The differences in the BAS determination approaches could be apparently explained by the chemical composition diversity of chamomile flowers. It should be mentioned that quality requirements of MPRM are of great importance either in the process of plant-based drugs development or when individual compounds extraction is performed.Conclusion. Thus the greatest differences between the chamomile flowers parameters have SF XIII and the foreign pharmacopoeias. SF XIII has the most detailed description of diagnostic signs of the medicinal plant raw material and the impurities in it. For the foreign pharmacopoeias there is a tendency to the quantitative analysis of the individual substances while in SF XIII chamomile flowers are standardized upon a sum of biologically active substances.